2020
DOI: 10.1097/sle.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Experience on Thoracoscopic Sleeve Lobectomy: Continuous Suturing Technique of the Bronchial Anastomosis in 12 Cases

Abstract: Background: Sleeve resection is a widely performed type of operation in the surgical treatment of non–small cell lung cancer. Video-assisted thoracoscopic surgery (VATS) is now used even in central tumor surgeries of the lung with the increasing technology and experience. Sleeve resection cases performed through VATS in our clinic in recent years were presented with demographic, surgical, pathologic, and survey characteristics. Materials and Methods: Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Our findings revealed that despite patients who underwent open surgeries generally requiring slightly more additional i.v. analgesics than those who received VATS, VATS was able to effectively alleviate the surgical‐related pain compared to thoracotomy, which was in line with previous studies analyzing other surgical modalities, including lobectomy, bronchial sleeve resection, and pneumonectomy 12,19,20 . This benefit of VATS was likely because of the smaller incisions created, which led to less tissue trauma, reduced inflammation, and fewer nerve injuries 21 .…”
Section: Discussionsupporting
confidence: 82%
“…Our findings revealed that despite patients who underwent open surgeries generally requiring slightly more additional i.v. analgesics than those who received VATS, VATS was able to effectively alleviate the surgical‐related pain compared to thoracotomy, which was in line with previous studies analyzing other surgical modalities, including lobectomy, bronchial sleeve resection, and pneumonectomy 12,19,20 . This benefit of VATS was likely because of the smaller incisions created, which led to less tissue trauma, reduced inflammation, and fewer nerve injuries 21 .…”
Section: Discussionsupporting
confidence: 82%
“…Zhou et al and Wang et al reported mean durations of anastomosis between 55 and 39 minutes, respectively [3,6]. In Ceylan et al the reported range of anastomosis time was 55-110 minutes [5]. In our study, the anastomosis times were 82 minutes in the first case and 65 minutes in the second.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that the incidence of these complications ranges from 4.8% to 31% [3,7]. Ceylan et al reported that, in their series of 12 cases, there was one case of myocardial infarction and one case of prolonged air leak [5]. Wang et al reported that there were no complications in their series [6].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations